Analisis Faktor-faktor yang Diperlukan pada Saat Membuka Tabungan Anak (Studi Kasus pada Tabungan BRI Junio) - , Isnugrahanti Dwita Pertiwi ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Children as a very potential market is seen as a target market, potential market and influnce market. Public awareness in savings is increased nowadays since the education on savings in the bank have taught from an early age. The children potential market on savings account has attracted many banks to work on it. Competition has increased due to several national and foreign bank had previously worked on childrenâs savings segment with various features and advantages that are almost the same. Appropriate strategy needs to be run by BRI to promote Tabungan BRI Junio and gain competitive advantage. The research was conducted to determine the strategy that has been run by BRI and âTabungan BRI Junioâ and identify the factors most considered by customers when opening a âTabungan BRI Junioâ. This research is exploratory and quantitative case study on Tabungan BRI Junio with factor analysis to determine whether the indicators forming a factor is located in these factor or not, or even form a new factor. Stage procedures performed included descriptive analysis via Kaiser-Meyer-Olkin Test (KMO) and Bartlettâs Test, Extraction and Rotation. Results showed there were ten factors that most considered by customers when opening a âTabungan BRI Junioâ : Branch Location, People Influence, ATM Service, Marketing Promotion, Non Physical Attractiveness, Service Provision, Physcal Attractiveness, Secure Feeling, Proximity, and Financial Benefit.